An Integrated Case Study for Evaluating the Impacts of an Oil Refinery Effluent on Aquatic Biota in the Delaware River: Introduction, Study Approach, and Objectives - Hall, Lenwood W.; Burton, Dennis T. (Human and ecological risk assessment, 2005)
This is the first in a series of article presenting results from a case study designed to assess the impacts of an oil refinery effluent [primarily polynuclear aromatic hydrocarbons (PAHs)] on aquatic biota in the Delaware River. During the course of the study, the oil refinery was owned by Motiva Enterprises LLC. This article provides background information on the study area, the study approach and objectives. The specific objectives of this multiyear study were to: (1) measure water column concentrations of PAHs and other contaminants (i.e., metals) in Motiva's effluent and intake canal and selected Delaware River sites; (2) assess fate and transport issues associated with the Refinery effluent; (3) characterize sediment PAHs, total organic carbon (TOC), and grain size distributions in the discharge canal, near-field, mid-field and far-field areas of the Refinery to aid in the selection of Triad sample sites (including reference areas); (4) conduct Triad studies (chemical characterizations, sediment toxicity assessments, and benthic community characterizations) at selected study sites during the spring and summer of 2001 and 2002; (5) perform fingerprinting of PAHs in Motiva's effluent to differentiate Motiva-related PAHs in sediment and biota from other sources; (6) assess bioavailability of PAHs, PCBs, and metals by using resident bivalve studies; (7) conduct long-term coring to determine potential impact of past non-complying discharges; and (8) integrate and analyze all study components to address the research goals. The results from objectives 1, 2, and 3 are briefly summarized in this series of articles whereas the other five objectives are the subject of the various papers presented in this volume.